Effect of Interest Rate on Economic Performance: A Case of Nepal - Niraula, Anush (Nepalese Journal of Finance, 2025)
This study examines the effect of interest rate on economic performance: A case of Nepal. Gross domestic product (GDP) is selected as the dependable variables. The selected independent variables are lending interest rate, deposit interest rate, net interest margin, total deposits and inflation. The study is based on data of 20 Nepalese commercial banks for the period from 2014/15 to 2020/21. The data were collected from economic survey published by Ministry of Finance, annual report of NRB supervision and economic bulletin of World Bank. The correlation coefficients and regression models are estimated to test the significance and effect of interest rate on economic performance in Nepal. The study showed that total deposit has a positive impact on GDP growth rate indicating that increase in total deposit leads to increase in GDP growth rate. Similarly, the result shows that there is a positive impact of net interest margin on GDP growth rate. It indicates that higher the net interest margin, higher would be the GDP growth rate. Further, the result shows that there is a negative impact of inflation rate on lending interest rate. It indicates that higher the inflation rate, lower would be the GDP growth rate. Moreover, the result shows that there is a positive impact of lending interest on GDP growth rate. It reveals that higher the lending interest rate higher would be the GDP growth rate. Similarly, the result shows that there is a positive impact of deposit interest on GDP growth rate. It implies that higher the deposit interest rate, higher would be the GDP growth rate.